An efficient algorithm for solving the conformable time-space fractional telegraph equations - ABDELKEBIR, Saad (Université de M'sila, 2021)
In this paper, an efficient algorithm is proposed for solving one dimensional time-space-fractional telegraph equations. The fractional derivatives are described in the conformable sense. This algorithm is based on shifted Chebyshev polynomials of the fourth kind. The time-space fractional telegraph equations is reduced to a linear system of second order differential equations and the Newmark’s method is applied to solve this system. Finally, some numerical examples are presented to confirm the reliability and effectiveness of this algorithm.
Keywords: Conformable fractional calculus, Newmark’s method, Shifted Chebyshev polynomials of the fourth kind, Time-space-fractional telegraph equation. 1.